2018
DOI: 10.1029/2018gc007493
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Orogenic Gold Mineralization and Crustal Shearing Along Ailaoshan‐Red River Belt, Southeastern Tibetan Plateau: New Constraint From Paleomagnetism

Abstract: A new perspective on the relationship between orogenic gold mineralization and crustal shearing is presented in this case study on the gold deposits along Ailaoshan‐Red River shear zone (ARSZ), southeastern Tibetan Plateau. The sinistral ductile shearing along the zone occurred from ca. 31 to 17 Ma resulting in a displacement of ~1,000 km. A series of orogenic gold deposits, represented by the Zhenyuan and Chang'an deposits, occur on western margin of the ARSZ. The timing of mineralization and its relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…the paleoposition of the Lüchun-Jinping microblock was spatially at same paleolatitude as the Binchuan and in the western part of the Binchuan area during most of its geological history (Xiao et al, 2003). Furthermore, the paleomagnetic data of the lamprophyres and mineralized intrusions from the Beiya ore district in western Yangtze Craton and from the Chang'an gold district in the Lüchun-Jinping microblock also support this inference (Gao et al, 2018a(Gao et al, , 2018b.…”
Section: The Compositional Zonation Constraints the Paleo-position Of...mentioning
confidence: 66%
“…the paleoposition of the Lüchun-Jinping microblock was spatially at same paleolatitude as the Binchuan and in the western part of the Binchuan area during most of its geological history (Xiao et al, 2003). Furthermore, the paleomagnetic data of the lamprophyres and mineralized intrusions from the Beiya ore district in western Yangtze Craton and from the Chang'an gold district in the Lüchun-Jinping microblock also support this inference (Gao et al, 2018a(Gao et al, , 2018b.…”
Section: The Compositional Zonation Constraints the Paleo-position Of...mentioning
confidence: 66%
“…33 Ma, was obtained and interpreted as the precise age of the Zhenyuan gold deposit (Wang et al, 2001;Deng et al, 2015). Recently, Gao et al (2018) suggested the ore-forming age of the Zhenyuan gold deposit is ca. 20 Ma by constraining the paleolatitude of mineralized rocks.…”
Section: Implication For Gold Mineralizationmentioning
confidence: 99%
“…Therefore, it is essential to understand different remagnetization mechanisms and to explore new research objects to conduct paleomagnetic studies in areas lacking suitable strata (Butler, 1992; Kent et al., 1987; X. Zhao & Coe, 1984). The ore deposits have proven to be a promising paleomagnetic research object due to the acquisition of remanence during mineralization (Gao et al., 2018, 2019; Symons et al., 1998). These studies have improved our understanding of the interaction between hydrothermal fluids and rocks, as well as how it affects rock magnetization.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao & Coe, 1984). The ore deposits have proven to be a promising paleomagnetic research object due to the acquisition of remanence during mineralization (Gao et al, 2018(Gao et al, , 2019Symons et al, 1998). These studies have improved our understanding of the interaction between hydrothermal fluids and rocks, as well as how it affects rock magnetization.…”
mentioning
confidence: 99%